Laughing your vote off: the impact of candidates’ humor on voters’ emotions and intentions - Mendiburo-Seguel, Andrés; Olah, Andrew R.; Paez, Dario; Navia, Patricio (Frontiers in Political Science, 2024)
Both the Theory of Affective Intelligence and the Expectancy Violation Theory suggest emotions are crucial in supporting political candidates. However, despite the considerable existing evidence on this topic, the impact of humor-induced emotions has been less explored. In this study, we examine whether positive and negative emotions mediate the effects of politicians’ use of affiliative humor on their likeability and citizen’s intention to vote for them. To do this, we designed an experiment in the context of the Chilean presidential elections of 2021, where two candidates representing extreme opposing ideologies competed for the office of president: Gabriel Boric, from a coalition including the Communist Party, and José Antonio Kast from the extreme-right Republican Party. Both candidates used different campaign techniques, including humor that did not always have political content. The experiment was run prior to the second round of the election with a sample of Chilean voters two months before the election (n = 1,033) and had four conditions: two experimental groups watched a video of a candidate using nonpolitical humor, and two control groups did not. Results indicate that humor boosted both candidates’ likeability and vote probability differently: for Boric, it increased positive emotions; for Kast, it reduced negative emotions. Perceptions of a candidate’s humor predicted higher likeability and declared probability of voting for him, independent of political stance. We discuss these outcomes through ITA and EVT frameworks and their significance for political communication.